1994
DOI: 10.1042/bj3000175
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of enzyme-bound calcium with strontium alters the kinetic properties of methanol dehydrogenase

Abstract: Methanol dehydrogenase (MEDH) possesses tightly bound Ca2+ in addition to its pyrroloquinoline quinone (PQQ) prosthetic group. Ca2+ was replaced with Sr2+ by growing the host bacterium, Paracoccus denitrificans, in media in which Ca2+ was replaced with Sr2+. MEDH, which was purified from these cells (Sr-MEDH), exhibited an increased absorption coefficient for the PQQ chromophore, and displayed certain kinetic properties which were different from those of native MEDH. Native MEDH exhibits an endogenous activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 39 publications
3
11
1
Order By: Relevance
“…The small spectral differences observed here for the hybrid Halo,,,-enzymes are not in agreement with the large difference in absorbance reported for SrZ -containing and Ca2 -containing methanol dehydrogenase enzymes [15]. However, on close inspection of the absolption spectra of the enzymes, it seems likely that the Srz+-enzyme was isolated in the fully reduced form and the Ca'+-enzyme in the usual semiquinone form [16], which could explain the large difference in absorbance (and the small difference in the maxima).…”
Section: Discussioncontrasting
confidence: 99%
“…The small spectral differences observed here for the hybrid Halo,,,-enzymes are not in agreement with the large difference in absorbance reported for SrZ -containing and Ca2 -containing methanol dehydrogenase enzymes [15]. However, on close inspection of the absolption spectra of the enzymes, it seems likely that the Srz+-enzyme was isolated in the fully reduced form and the Ca'+-enzyme in the usual semiquinone form [16], which could explain the large difference in absorbance (and the small difference in the maxima).…”
Section: Discussioncontrasting
confidence: 99%
“…The catalytic role of PQQ complexed Ca 2ϩ is 3-fold: (i) modest reduction of the pK a of CH 3 -OH, (ii) polarizing the carbonyl group at the C-5 position of the PQQ moiety, and (iii) placing the reaction components in position to react. The proposed role of Ca 2ϩ is also in agreement with a recent study on strontium (Sr 2ϩ ) substituted MDH (36). Similar mechanisms could also be operative in other quinoproteins such as other alcohol and glucose dehydrogenases.…”
Section: Discussionsupporting
confidence: 77%
“…analyzed MxaF‐MDH in the presence of both Ca 2+ and Ba 2+ and found no difference in the absorbance maximum upon substitution with those two metal ions in the active site of the MDH from M. extorquens . However, Harris and Davidson reported that the extinction coefficient of PQQ in the purified MDH was altered when Ca 2+ was replaced by Sr 2+ in the purification medium of Paracoccus denitrificans , although this observation can also be explained in terms of contamination with other proteins because the total ratio of the peaks at 280 and 345 nm was used for this interpretation . A peak maximum at 355 nm seems to be typical for the MDH of the XoxF‐type isolated from M. fumariolicum SolV, whereas the UV/Vis spectrum of the related Ca‐MDH from M. extorquens shows this peak at 345 nm.…”
Section: Resultsmentioning
confidence: 99%